АТРИБУТИВ БИРИКМАЛАР СТАТИСТИК ПАРАМЕТРЛАРИ ЎЗБЕК АДАБИЙ ТИЛИ УСЛУБЛАРИ ДИФФЕРЕНЦИАЛ БЕЛГИЛАРИНИНГ ИФОДАЧИСИ СИФАТИДА - Хўжаниёзов, Э.; Айтбаева, А. (SCIENCE and SOCIETY, 2019)
In the article the scientific and belles-lettres styles are differentiated as separate functional styles at the level of attributive word combinations. The statistical parameters of attributive word combinations of the model «adjective+noun» differentiate these styles on the inter style and intra style levels. They are quantitative and qualitative indicators of these styles.